Comparing driller’s and engineer’s methods to control kick for basement reservoirs - Sharafaddin, Osama (2019)
There are various difficulties involved in drilling operations in the oil and gas industry. Well control is considered the most vital one. Well control systems are applied when a kick is detected entering the wellbore from the formation. Kicks occur when formation pressure is greater than wellbore pressure causing an influx of gas into the wellbore. Uncontrolled gas kicks have the potential to cause a blowout, resulting in financial loss, possibility of injury, loss of live, and pollution. Once a gas kick is detected, it has to be circulated out safely and efficiently to surface. While the influx of gas migrates in the wellbore toward the surface, it affects different parameters such drill pipe pressure, annulus pressure, fracture pressure, bottomhole pressure, and casing shoe pressure. This work investigates and analyses these pressure changes that act on these parameters during well control. A Drillbench simulator was used to conduct a comprehensive comparison between the Driller’s and Engineer’s method to determine the most effective method to kill the well in basement reservoirs. A case study was conducted on a Masila basement reservoir, since fractured basement is becoming an important oil and gas contributor to the petroleum industry. Engineer’s method showed better results and more advantages over Driller’s method since it would require only one circulation to kill the well and no potential for further kicks. The sensitivity analysis proved that kick size and kick intensity have significant effect while circulating the kick. The bigger the size of kick the higher pressure profile was noticed. Similarly, an increase in kick intensity would result in increasing choke pressure, casing shoe pressure and pump pressure.